Probing the potential of the Shark Panel InDel multiplex v2.0 on the forensic identification of batoid elasmobranchs. (December 2017) - Amaral, C.R.L.; Bitencourt, A.; Teixeira, C.; Pereira, F.; Silva, D.A.; Amorim, A.; Carvalho, E.F.
Abstract: The Elasmobranchii comprises the diverse and important group of sharks and rays. The group includes some of the ocean's largest predatory fishes, suffering unsustainable fishing activities and is commercially overexploited for their meat and fins. Overfishing has resulted in significant population declines and several species are now considered under high threat and facing extinction, with about 93% of its nominal species included in the IUCN Red List. Molecular data have provided important information about these species, allowing the management of natural stocks and preventing their decline. Population genetics and connectivity data knowledge are now available and play an important role on establishing conservation policies. However, despite the ecological, commercial and conservation importance, no molecular method is available to identify sharks and rays in a forensic context. Following the development of the Shark Panel v1.0 which includes uniquely sharks, now we tested the effectiveness of the v2.0 multiplex on batoid elasmobranchs. We carried out a systematic molecular analysis using 85 previously published mitochondrial 16S rRNA gene sequences obtained from the NCBI database and found that indels in the 16S rRNA gene can be used to distinguish several analyzed species, including some of the most threatened according to IUCN Red List. The regions selected in this study can be used for the construction of molecular identification assays.